LIVER HEMANGIOMA ULTRASOUND TEST AND EXAMINATION ADVANTAGES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Liver neoplasms represent a diverse group of tumors of benign and malignant nature. Their differential diagnosis often causes certain difficulties. At the present stage of the development of diagnostic methods, there is a need to choose a non-invasive, highly informative and minimally sufficient research method for solving diagnostic problems, influencing the choice of further therapeutic and diagnostic tactics. Ultrasound examination using modern technologies has advantages in the diagnosis of focal liver damage. The article discusses the ultrasound differential diagnostic signs of focal liver neoplasms using various ultrasound diagnostic methods.